P215 Referral Patterns For Mediastinal Staging With Ebus Across A Lung Cancer Network A Report From The Manchester Cancer Ebus Sub-group. (10th November 2014) - Evison, M; Crosbie, P; Morris, J; Martin, J; Shah, R; Doran, H; Hoyle, J; Bailey, S; Rana, D; Sundar, R; Booton, R
Abstract : Introduction: Manchester Cancer is a large Cancer Network in the North West of England, consisting of ten NHS Trusts. There is known variability in lung cancer outcomes across the ten trusts, including resection rates. We have examined the referral patterns of each individual trust for EBUS mediastinal staging and compared this with the trust's lung cancer resection rates. Methods: The Manchester Cancer EBUS sub-group has data for all EBUS referrals from each of the ten NHS trusts in our Network in 2012. The National Lung Cancer Audit Report 2013 provides the number of lung cancer patients diagnosed at each trust for the same time period. From this data we could estimate the proportion of lung cancer patients from each trust that were referred for mediastinal staging with EBUS. Results: In 2012, 2302 patients were diagnosed with lung cancer in this Network. In the same period, 193 patients were referred for EBUS mediastinal staging (8.4%). The proportion of lung cancer patients referred for mediastinal staging with EBUS varied significantly across the ten trusts ranging from 3.4% to 30.2% (p < 0.0001). The spearman co-efficient was 0.60 (p = 0.07) suggesting a possible relationship between the proportion of patients referred for EBUS and surgical resection (Figure 1). However, this may be due to a very high rate of staging EBUS at one trust, which if excluded yields a spearman co-efficient of 0.45 (p = 0.22). Discussion: It is highly concerning that only 8% of lung cancer patients underwent EBUS nodal staging in our network given 52% of UK patients with histologically confirmed NSCLC are stage I-III at the time of diagnosis. It is of note that the Trust with the highest proportion of patients undergoing EBUS nodal staging have the highest surgical resection rate and three of the four Trusts with the lowest resection rates refer <5% of patients for EBUS nodal staging. Standardisation of referral practice across the Network is a key future goal for the EBUS Sub-group.